2010
DOI: 10.1007/s10578-010-0191-4
|View full text |Cite
|
Sign up to set email alerts
|

Normative Data on Anxiety Symptoms on the Multidimensional Anxiety Scale for Children in Taiwanese Children and Adolescents: Differences in Sex, Age, and Residence and Comparison with an American Sample

Abstract: The aims of this study were to examine the differences in the levels of anxiety symptoms on the Taiwanese version of the Multidimensional Anxiety Scale for Children (MASC-T) between Taiwanese children and adolescents and the original American standardization sample across gender and age, and to examine differences in sex, age, and residential background in the levels of anxiety symptoms. A total of 10,566 Taiwanese children and adolescents in the community completed the MASC-T. Their levels of anxiety symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 22 publications
2
22
2
2
Order By: Relevance
“…Participants in this study were recruited from the 2009 Project for the Health of Children and Adolescents in Southern Taiwan, a research program examining the mental health status of children and adolescents living in four counties and three metropolitan areas in southern Taiwan 23 . In 2009, 254,130 students were studying in 205 junior high schools and 202,883 students in 143 senior high/vocational schools in this area.…”
Section: Participantsmentioning
confidence: 99%
“…Participants in this study were recruited from the 2009 Project for the Health of Children and Adolescents in Southern Taiwan, a research program examining the mental health status of children and adolescents living in four counties and three metropolitan areas in southern Taiwan 23 . In 2009, 254,130 students were studying in 205 junior high schools and 202,883 students in 143 senior high/vocational schools in this area.…”
Section: Participantsmentioning
confidence: 99%
“…Third, no study has examined the moderating effects of socio-demographic characteristics on the relationship between anxiety symptoms and QOL. Research found that there are gender differences in both QOL [11] and anxiety symptoms [12]. There are also differences in anxiety symptoms between adolescents living in rural and urban areas [12].…”
Section: Introductionmentioning
confidence: 98%
“…Research found that there are gender differences in both QOL [11] and anxiety symptoms [12]. There are also differences in anxiety symptoms between adolescents living in rural and urban areas [12]. Meanwhile, parents' education level has influence on adolescents' mental health [13].…”
Section: Introductionmentioning
confidence: 99%
“…Berbeda dengan remaja awal, remaja akhir yang merupakan masa persiapan menuju dewasa, terjadi peningkatan kemampuan berfikir. Pada masa ini risiko terjadi peningkatan ansietas seiring dengan meningkatnya tuntutan sebagai remaja akhir (Yen, et al, 2010).…”
Section: Pendahuluanunclassified
“…Tekanan orang tua agar siswa lulus dengan prestasi yang memuaskan, sehingga mendapat tempat di perguruan tinggi favorit, tingginya persaingan untuk memasuki dunia kerja dan persiapan untuk hidup mandiri terpisah dari orang tua merupakan sumber ansietas siswa yang berusia remaja akhir atau yang berpendidikan SMA (Karatas, Alci, & Aydin, 2013;Santrock, 2007;Yen, et al, 2010). Akan tetapi, hasil penelitian ini menunjukkan bahwa mayoritas siswa SMA hanya mengalami anisetas ringan.…”
Section: Pembahasanunclassified